THE EMERGENCE AND MANIFESTATION OF THE MOVARUNNAHR SCHOOL OF FIQH (American Journal of Interdisciplinary Research and Development, 2023)
It is known that at the end of the 8th century and at the beginning of the 9th century, the Hanafi sect of the Sunnis of Islam began to spread in Movarounnahr. In the cities of Bukhara and Samarkand, the Movarounnahr school of jurisprudence was established based on the teachings of this sect. The jurists of Movarounnahr gained great fame in the Islamic world with their profound knowledge and valuable works.